INFECTIOUS DISEASES CAUSED AFTER RENAL TRANSPLANTATION (Scientific Conference on Multidisciplinary Studies, 2025)
The evaluation of infections in transplant recipients involves consideration of both the donor and the recipient of the transplanted organ. Infections after transplantation are complicated by the use of drugs that are necessary to enhance the likelihood of survival of the transplanted organ, but that also cause the host to be immunocompromised. Thus what might have been a latent or asymptomatic infection in an immunocompetent donor or in the recipient before therapy can become a life-threatening problem when the recipient becomes immunosuppressed.